A Study on Cost Effectiveness and Security of VANET Technologies for Future Enhancement. (2016) - Chirayil, Greeshma S.; Thomas, Ashly
Abstract: Intelligent Transport System (ITS) is an advanced application which provides web enabled services for traffic and transport system, which results in a safer, coordinated traffic network system. ITS is very effectively used in VANET (Vehicular Ad-hoc Network), which is a spontaneous creation of wireless network of vehicles for exchanging information between them, for improved transport and traffic management and to enable various users to be sufficiently informed about the road and make safer and smarter decisions on road by using transport networks. As the technology has to be used widely, there is a high need for a low cost VANET technology with high security and Quality of Service. To go for any further developments, a thorough analysis on the available technologies is essential to get a closer view on the current scenario. The result of this study can open doors for a better technology for future VANETs. This paper considers a few existing technologies such as CROWN, Vehicular Cloud and VANET-Cloud and a comparison on these is carried out.